2004
DOI: 10.1097/00002030-200409030-00017
|View full text |Cite
|
Sign up to set email alerts
|

Indinavir increases glucose production in healthy HIV-negative men

Abstract: In the absence of HIV infection, changes in adipose tissue and lipid levels, HIV protease inhibitor therapy increases fasting glucose levels,suggestive of hepatic insulin resistance. After 4 weeks of indinavir treatment in nine HIV-negative healthy men, fasting glucose production and glycogenolysis were significantly increased. During the euglycemic hyperinsulinemic clamp, indinavir blunted the ability of insulin to suppress glucose production. Therefore, indinavir worsens hepatic insulin sensitivity, increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 11 publications
2
24
0
Order By: Relevance
“…Previously, multiple studies have described the relationship between IR and the use of HAART, particularly PIs and some NRTIs. It has been shown that some PIs such as lopinavir or indinavir increase insulinemia in healthy volunteers (22,30,31), although it is debated whether this could be compensated in prolonged treatments (32). PIs could inhibit proteases responsible for conversion of proinsulin into insulin, as well as protease regulating insulin catabolism, generating a state of hyperinsulinemia and hyperglycemia (33).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, multiple studies have described the relationship between IR and the use of HAART, particularly PIs and some NRTIs. It has been shown that some PIs such as lopinavir or indinavir increase insulinemia in healthy volunteers (22,30,31), although it is debated whether this could be compensated in prolonged treatments (32). PIs could inhibit proteases responsible for conversion of proinsulin into insulin, as well as protease regulating insulin catabolism, generating a state of hyperinsulinemia and hyperglycemia (33).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with indinavir (protease inhibitor) for four weeks, of individuals not infected with HIV promoted an increase in the levels of glucose and a 20% reduction in insulin sensitivity 46 . Schwarz et al 47 also showed a 17% decrease in insulin sensitivity, associated with an increase in the production of glucose and glycogenolysis, indicating that indinavir induces peripheral insulin resistance and increases the production of endogenous glucose. It is noteworthy that this condition may be associated with HIV infection, probably by direct action of the virus on pancreatic β-cell function or in the mechanism of action of insulin 48 .…”
Section: Changes In Glycolytic Metabolicmentioning
confidence: 96%
“…Compared with administration of low-dose RTV alone, co-administration of darunavir resulted in slightly lower RTV C max (563 vs. 669 ng Á h/mL) and AUC 24 h (4729 vs. 5442 ng/h/mL) values, whereas coadministration of atazanavir and RTV led to higher RTV C max (1120 vs. 691 ng/mL) and AUC 24 h (9277 vs. 5717 ng/h/ mL) values. Relative to treatment with low-dose RTV alone, the least squares mean ratios (90% CIs) for RTV C min , C max and AUC 24 …”
Section: Effect Of Darunavir and Atazanavir On Rtv Pharmacokineticsmentioning
confidence: 99%